Turkish Teachers' Response to the COVID-19 Crisis: Challenges and Opportunities - Kucukakin, Pinar Mercan; Demir, Cennet Gologlu; Gokmenoglu, Tuba (Egitim ve Bilim, 2022)
The present study examined teachers' perceptions of changes in their professional lives brought about by distance education during the COVID-19 outbreak. It was also aimed to explore how this particular global crisis and unprecedented times of education have affected teachers' motivation and their perceptions of the teaching profession. Twenty-two teachers working at different levels and types of K–12 schools in different cities in Turkey were interviewed by utilizing a phenomenological qualitative inquiry method. Our analysis showed that the obligatory transition to distance education created new opportunities and challenges for both teachers and students. While the teachers had emotional exhaustion, stress, and professional difficulties; distance education helped them develop new skills to better integrate educational technologies into classroom teaching. The findings also indicated that the COVID-19 crisis reinforced deep-rooted inequities in the Turkish education context. This study offers several implications for policymakers and educators to plan educational recovery from COVID-19. Bu çalışmada, COVID-19 salgını sırasında uygulanan uzaktan eğitimin öğretmenlerin mesleki yaşamlarında yol açtığı değişikliklere ilişkin algıları incelenmiştir. Ayrıca küresel krizin ve daha önce benzeri görülmemiş eğitim sürecinin öğretmenlerin motivasyonunu ve öğretmenlik mesleğine ilişkin algılarını nasıl etkilediği de araştırılmıştır. Nitel araştırma yöntemlerinden biri olan olgubilim deseninde tasarlanan çalışmada, farklı düzey ve türdeki K–12 okullarında görev yapan, Türkiye'nin farklı illerinden yirmi iki öğretmenle görüşülmüştür. Bulgular, uzaktan eğitime zorunlu geçişin hem öğretmenler hem de öğrenciler için yeni fırsatlar ve zorluklar yarattığını göstermiştir. Öğretmenler duygusal tükenmişlik, stres ve mesleki zorluklar yaşamış, ama aynı zamanda uzaktan eğitim, öğretmenlerin eğitim teknolojilerini sınıf öğretimine daha iyi entegre edebilmeleri için de yeni beceriler geliştirmelerine yardımcı olmuştur. Bununla birlikte, bulgular, COVID-19 krizinin Türkiye’deki eğitim bağlamında köklü eşitsizlikleri daha da derinleştirdiğini ortaya koymuştur. Bu çalışma, politika yapıcılara ve eğitimcilere COVID-19'dan hareketle eğitimsel iyileşmeyi planlayabilmeleri için çeşitli çıkarımlar sunmaktadır.